2021
DOI: 10.3390/foods10092001
|View full text |Cite
|
Sign up to set email alerts
|

Eating Competence among Brazilian Adults: A Comparison between before and during the COVID-19 Pandemic

Abstract: The coronavirus pandemic started a worldwide emergency, and tight preventive actions were necessary to protect the population, changing individuals’ daily habits. Dwelling and working at home can change dietary habits, affect food choice and access, as well as the practice of physical activity. In this regard, this study’s goal was to compare eating competence (EC) among Brazilian adults before and during the coronavirus pandemic, using the Brazilian version of the eating competence Satter inventory (ecSI2.0™B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Young adults outside of academia also experience major transitions and stress, and may be at even higher risk of developing food insecurity and poor eating competence due to intergenerational transmission of maladaptive eating behaviors ( Berge, R., Larson, Miller, & Neumark-Sztainer, 2018 ). Although existing literature on eating competence includes various age groups and populations ( Krall & Lohse, 2011 ; Lohse et al, 2012 ; Psota et al, 2007 ; Queiroz et al, 2021 ; Tilles-Tirkkonen et al, 2019 ), none to our knowledge have focused on young, non-student adults. This is another area ripe for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Young adults outside of academia also experience major transitions and stress, and may be at even higher risk of developing food insecurity and poor eating competence due to intergenerational transmission of maladaptive eating behaviors ( Berge, R., Larson, Miller, & Neumark-Sztainer, 2018 ). Although existing literature on eating competence includes various age groups and populations ( Krall & Lohse, 2011 ; Lohse et al, 2012 ; Psota et al, 2007 ; Queiroz et al, 2021 ; Tilles-Tirkkonen et al, 2019 ), none to our knowledge have focused on young, non-student adults. This is another area ripe for future research.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study performed in Brazil from 30 April to 31 May 2021 among a convenience sample of the Brazilian adult population (n = 302; 76.82% female) found that the measure of the contextual skills component decreased after the pandemic among those who gained weight (9.56 ± 3.43vs. 7.50 ± 3.95; p < 0.005); those who decreased the consumption of vegetables (9.78 ± 2.79 vs. 6.63 ± 3.40; p < 0.005), and those who increased the consumption of sugary beverages (9.19 ± 3.16 vs. 6.92 ± 3.70; p < 0.005) [66]. Moreover, individuals who used to buy ready-to-eat meals during the pandemic showed a reduction in total EC and all components (p < 0.005).…”
Section: Contextual Skillsmentioning
confidence: 97%
“…The decline in total food spending could likely translate into reduced calorie intake or poor quality food consumption, compounding consumer health risks and food security situations ( 20 , 21 ). Moreover, the pandemic may have changed the attitudinal and behavioral views of consumers about foods, as indicated by lowered eating competence ( 22 ). The individual consumption pattern was also affected by the epidemic ( 23 ).…”
Section: Introductionmentioning
confidence: 99%